Mast cell density and its clinical relevance in Waldenström's macroglobulinemia. Issue 2 (8th February 2022) - Lemal, Richard; Poulain, Stéphanie; Ledoux‐Pilon, Albane; Veronese, Lauren; Tchirkov, Andrei; Lebecque, Benjamin; Tassin, Thomas; Bay, Jacques‐Olivier; Charlotte, Frédéric; Nguyen‐Khac, Florence; Berger, Marc; Godfraind, Catherine; et al.
Abstract: The presence of numerous mast cells (MCs) mixed with tumor cells in the bone marrow (BM) is a hallmark of the diagnosis of Waldenström's macroglobulinemia (WM). MCs have been shown to support lymphoplasmacytic cell growth, but there is thus far no demonstration of the prognostic impact of BM MC density in WM. We investigated BM MC density by sensitive and specific digital quantification, allowing the analysis of a large area infiltrated by BM tumor cells. A total of 65 WM patients were investigated, including 54 at diagnosis and 11 at relapse. Tryptase and CD20 immunohistochemisty staining was performed on contiguous sections of deparaffinized BM trephine biopsies. After numerization of each section, the BM surface area was manually marked out, excluding the bone framework and adipocytes to limit the analyses to only hematopoietic tissue. MCs were assessed using a digital tool previously used to quantify immune‐cell infiltrates on tumor‐tissue sections. Deep next‐generation sequencing and allele‐specific PCR were used to explore the MYD88 and CXCR4 mutational status. MC density was heterogeneous among the WM patients. An optimal MC density threshold (> 56 MC.mm –2 ) was defined according to ROC curve analysis of overall survival. A higher MC density (> 56 MC.mm –2 ) was associated with greater BM involvement by WM lymphoplasmacytic cells and less hepatosplenic involvement ( p  = 0.023). Furthermore, MC density significantly correlated with a higher ISSWM score ( p  = 0.0003) in symptomatic patients. Patients with a higher MC density showed shorter median OS (56.5 months vs. nonreached, p  = 0.0004), even in multivariate analysis after controlling for other predictive variables, such as age, ISSWM score, and CXCR4 mutational status. In conclusion, MC density can be accurately measured in WM patients using a specific digital tool on well‐outlined hematopoietic tissue surfaces. High MC density is associated with aggressive features and a poor clinical outcome, emphasizing the need for further investigation of the involvement of MCs in the pathophysiology of WM.